2016
DOI: 10.1099/jgv.0.000371
|View full text |Cite
|
Sign up to set email alerts
|

Development of viable TAP-tagged dengue virus for investigation of host–virus interactions in viral replication

Abstract: Dengue virus (DENV) is a mosquito-borne flavivirus responsible for life-threatening dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS). The viral replication machinery containing the core non-structural protein 5 (NS5) is implicated in severe dengue symptoms but molecular details remain obscure. To date, studies seeking to catalogue and characterize interaction networks between viral NS5 and host proteins have been limited to the yeast twohybrid system, computational prediction and co-immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…It is important to highlight the consistent appearance of two members of this particle CD2BP2 and the helicase DDX23. In addition, previously identified partners of NS5 such as STAT2 and UBR4, and the splicing proteins PRPF8 and SNRNP200 were also detected [21,33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight the consistent appearance of two members of this particle CD2BP2 and the helicase DDX23. In addition, previously identified partners of NS5 such as STAT2 and UBR4, and the splicing proteins PRPF8 and SNRNP200 were also detected [21,33]. …”
Section: Resultsmentioning
confidence: 99%
“…About 20% of the proteins identified were previously associated with NS5 or DENV infection. These proteins include STAT2, THRAP3, PRPF8, SNRNP200 and UBR4 that have been recently reported to interact with DENV NS5 [21,33], ERC1 that was found to be downregulated during DENV infection [59], and ILF3 that also interacts with the viral NS3 protein [60]. Because NS5 was proposed to function as an adaptor for the ubiquitination system in association with UBR4, and the screen also identified UBR5 as NS5 binder, it will be interesting to further evaluate whether this ubiquitin ligase is involved in NS5-mediated proteasome degradation of specific host factors.…”
Section: Discussionmentioning
confidence: 99%
“…This approach distinguishes between prelysis and post-lysis interactions by identifying non-specific postlysis interactions due to the increased proportion of heavy relative to light isotopes (Carpp et al, 2014). In a fourth pulldown study (Poyomtip et al, 2016), a full-length DENV-2 construct (strain 16681) with tandem affinity purification (TAP)-tagged NS5 containing a poly-histidine and FLAG tags (inserted following N173 in MTase domain of NS5) was propagated in BHK21 cells followed by infection in Huh-7 cells. The NS5 complexes were isolated via FLAG-IP and analyzed by mass spectroscopy.…”
Section: Pull-down Studiesmentioning
confidence: 99%
“…The NS5 complexes were isolated via FLAG-IP and analyzed by mass spectroscopy. This study revealed 97 NS5 interactors, prominent among them being heterogeneous nuclear ribonucleoproteins (hnRNPs) and proteins involved in lipid metabolism (Poyomtip et al, 2016).…”
Section: Pull-down Studiesmentioning
confidence: 99%
“…Again, the tag insertion should not sterically hinder receptor binding. Although not used to identify viral receptors, this approach has been used to identify virus-host interactions, involved in replication within dengue virus serotype 2 (DENV-2) [113]. Here, the full-length DENV-2 RNA genome containing a polyhistidine and FLAG-tagged NS5 was synthesised in vitro using T7 RNA polymerase.…”
Section: Affinity Purification-mass Spectrometrymentioning
confidence: 99%